STUDI POTENSI LINGKUNGAN FISIK RUMAH TANGGA TERHADAP KEJADIAN ISPA PADA BALITA: Training; Nurse; Emotional intelligence. - Lili Eky Nursia N; Teungku Nih Farisni; Yarmaliza Yarmaliza; Fitriani Fitriani; Fitrah Reynaldi; Zakiyuddin Zakiyuddin (Jurnal Maternitas Kebidanan, 2020)
Acute Respiratory Infection (ARI) is an acute respiratory disease caused by an infectious agent that is transmitted from person to person. Symptoms include fever, cough and soreness in the throat, coryza (runny nose), shortness of breath, and difficulty breathing. Based on a preliminary study of 7 mothers of children under five at the Ujong Patihah Health Center, there was no ventilation according to requirements, and there were even houses that were not ventilated. The research objective was to determine the relationship between ventilation and house building with the incidence of Acute Respiratory Infection (ARI) in children under five. This research method used analytic survey design with cross sectional survey approach. The population in this study were all mothers who had 638 toddlers and a sample of 86 people. The sampling technique was random sampling and analyzed by univariate and bivariate using the chi-square test. The results showed that there was a significant relationship between ventilation and house building factors with ISPA under five. Pvalue <α = 0.05. It is concluded that there is a significant relationship between ventilation, and house building area with the incidence of Acute Respiratory Infection (ARI) in children under five. It is hoped that the next research can be done with a choice of other variables to see the risk factors for the incidence of ARI in toddlers. Keywords: Toddler ARI; house building area; ventilation.